2019
DOI: 10.1186/s12958-019-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Egg freezing for fertility preservation and family planning: a nationwide survey of US Obstetrics and Gynecology residents

Abstract: BackgroundLittle is known about resident attitudes toward elective egg freezing (EF) or how educational exposure to EF affects residents’ views and ability to counsel patients. This study aimed to evaluate US OB/GYN residents’ views on elective EF, decisions regarding family planning, and whether education on EF affects these views and self-reported comfort discussing EF with patients.MethodsA 32 question survey was emailed to program directors at all US residency programs for distribution to residents. Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 8 publications
(12 reference statements)
3
20
0
Order By: Relevance
“…Our response rate calculation is imprecise as the exact number of residents who actually received the recruitment email from their residency directors is unknown. If all residents did have access to the survey, the response rate would be approximately 4%, a magnitude consistent with other published survey research of obstetrics and gynecology residents through email recruitment -at 2.2% and 5% respectively (17,18). It is impossible to ensure that the survey was received by all of the intended recipients.…”
Section: Resultssupporting
confidence: 53%
“…Our response rate calculation is imprecise as the exact number of residents who actually received the recruitment email from their residency directors is unknown. If all residents did have access to the survey, the response rate would be approximately 4%, a magnitude consistent with other published survey research of obstetrics and gynecology residents through email recruitment -at 2.2% and 5% respectively (17,18). It is impossible to ensure that the survey was received by all of the intended recipients.…”
Section: Resultssupporting
confidence: 53%
“…Our earlier study of 241 Obstetrics & Gynecology residents reported an infertility rate of 8%, utilization of fertility preservation services of 2%, and that the majority of residents facing fertility issues felt little or no support from their programs [9]. Another survey of 113 Obstetrics & Gynecology residents and fellows reported that 71.8% postponed childbearing due to medical training, and that only half of female residents felt comfortable educating patients about oocyte cryopreservation [10]. A separate study of 238…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we believe the common themes emerging from our study still have merit in raising awareness around the prevalence of infertility/RPL among medical trainees as well as the need for additional resources for this population, and are important to inform GME policy in the future. Additionally, our survey size is still larger than other prior studies of similar subject in medical trainees, and the largest study on this subject [9,10,11,12,13,14,15]. However, further study is needed in larger samples to validate and generalize these findings across medical trainees.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Single status is consistently identified to be a major motivating factor in a number of studies assessing perceptions across varying populations. [13][14][15][16][17][18] Although of interest,…”
Section: Discussionmentioning
confidence: 99%